Oil's endless bid taming the unreliable price of oil to secure our economy - Dicker, Dan, 1960- (John Wiley & Sons, 2011)
"Expert analysis of rising oil prices and the out-of-control oil markets that jeopardize both national security and the economy. The price of oil is negatively impacting both companies and consumers. In Oil's Endless Bid: Taming the Unreliable Price of Energy to Secure Our Economy, energy analyst Dan Dicker recalls his experiences as an oil trader and reveals the changes that have taken place in the oil markets during the past twenty years, and particularly the last five, as investment banks, energy hedge funds, and managed futures funds have come to dominate energy trading and wreak havoc on prices. Reveals why oil prices cannot stabilize without dramatic action on the part of both government and business. Details how the novel, but wrong, idea of oil as an asset class took a sleepy, club-like market into the national spotlight. Describes how the United States is unnecessarily handing its wealth over to foreign oil producers during a time when the potential supply of oil is greater than ever. Written by an industry insider, Oil's Endless Bid analyzes the biggest financial story of the last ten years, how we lost control of our oil markets"--